Culture Media in Pharmacopoeial Analysis: Use, Current Requirements, Standardisation - S. M. Sukhanova; N. E. Zakharova (Биопрепараты: Профилактика, диагностика, лечение)
Culture media with predetermined specific characteristics play a key role in ensuring safety, quality and efficacy of medicinal products, especially biologicals. It is necessary to formulate clear criteria for culture media suitability, because they are used not only in manufacture, but also in quality control of medicinal products. The expansion of the range of complex high-technology medicinal products containing biologically derived substances as active ingredients, whose quality and properties are tested by biological methods, calls for more stringent requirements for the quality of culture media. The aim of the study was to analyse requirements for the culture media used in the production of medicinal products — in order to identify approaches to the development of a national standard. Currently, culture media are not included into the State Register of Medicinal Products, and there are no standards that could be used by manufacturers to confirm that a culture medium complies with specific safety, efficacy and quality requirements. The paper summarises the results of the analysis of the State Pharmacopoeia of the Russian Federation, 14th ed., and nine leading world pharmacopeias’ requirements for culture media used for various purposes (manufacture, auxiliary purposes, and quality control). Most countries have adopted requirements mainly for those culture media that are used in purity tests. The analysis revealed differences both in the lists of requirements (test strains, incubation and storage conditions, preparation for use, suitability assessment), and the approaches to the establishment and presentation of requirements. The paper discusses the main challenges and risks associated with the quality control of culture media in accordance with the requirements of the State Pharmacopoeia of the Russian Federation, 14th ed. It outlines current national and international ways of improving the quality of culture media used in the production of medicinal products, and substantiates the need to develop an appropriate national standard. The paper suggests approaches to the development and standardisation of requirements for the quality of various types of media used in the production and control of medicines. These approaches could be used in the preparation of the general chapter Culture media.